12‐Step Facilitation reduces damage from substance use in youths. Issue 9 (September 2017) - Unknown
Abstract : A pilot study helps to fill a gap in research on 12‐Step‐oriented approaches in treatment, finding that 12‐Step Facilitation (TSF) helped to reduce consequences related to substance use in young people ages 14 to 21. A significant aspect of the study, beyond being the first to test TSF in an adolescent population, is that the intervention overall compared favorably against a motivational enhancement therapy (MET)/cognitive behavioral therapy (CBT) approach that researchers referred to in their paper as "gold‐standard" outpatient treatment for youths.